The time frame of the insurance contract (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The present paper analyses the insurance contract duration which is an essentialelement of the insurance, as it will determinate the moment when the insurancerelation will start and finish, and therefore, the term during which the risk will becovered by the insurer. The insurance duration shall be clearly fixed on the policy, being necessary to settle if the contract could be extended or not. This extension of the insurance duration is not obligatory and the contractual parties could oppose toit. However, this term extension would imply in any case, the continuity of the insurance relation initially agreed by the parties.
Keywords: contract relation duration; contract extension